Use of Medical Devices in Hospice for Symptom Management. (December 2016) - Shah, Nidhi; Homel, Peter; Breznay, Jennifer
Background: Home health services in the United States(US) have been on a rise. Hospice patients cope with diverse physical and pain symptoms; medical devices are used for symptom management to improve their quality-of-care at end-of-life. Objective: Using the National Home and Hospice Care Survey (NHHCS), the study summarizes medical device use for symptom management and tracks various demographic variables for home hospice patients. Methods: A cross-sectional analysis of data using the 2007 NHHCS was conducted. There were 4733 hospice discharges which corresponded to 2, 505, 011 individuals in US with sampling weights. The data was analyzed using chi square tests and confounding factors adjusted with logistic regression. Results: Eighty-nine percent of hospice discharges were evaluated for pain at first assessment. The regression model for pain at first assessment was significantly associated with use of patient controlled analgesia (OR = 1.82, 95% CI = 1.28, 2.59) and urinary catheters (OR = 1.16, 95% CI = 1.02, 1.33). Patient with dyspnea were associated with significant use of oxygen (OR = 3.00, 95% CI = 2.64, 3.40) and metered dose inhaler (OR = 2.43, 95% CI = 1.92, 3.07). There was negligible use of total parenteral nutrition (TPN) noted in the study. Conclusion: In conclusion, the study highlights medical device use in home hospice care for end-of-life symptom management. It noted the significant use of IV infusion pumps and patient controlled analgesia. Conversely, there is little use of TPN or CPAP in patients with anorexia or dyspnea. While missing data on critical symptom evaluations regrettably raises questions about the validity of the study, the NHHCS serves as an important reservoir of data on the growing population of home hospice patients.